2020
DOI: 10.1115/1.4047133
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic System to Measure Neonatal Lung Compliance Over Late Stage Development as a Functional Measure of Lung Tissue Mechanics

Abstract: Premature birth interrupts the development of the lung, resulting in functional deficiencies and the onset of complex pathologies, like bronchopulmonary dysplasia (BPD), that further decrease the functional capabilities of the immature lung. The dysregulation of molecular targets has been implicated in the presentation of BPD, but there is currently no method to correlate resultant morphological changes observed in tissue histology with these perturbations to differences in function throughout saccular and alv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…The second step is to study the effect of PC on the therapeutic performance of nanocarriers such as drug release. This should be done by incorporating more physiological 3D in vitro models [218] and systems that incorporate flow [219,220], mechanical forces [221][222][223], and multicellular populations [224,225] for in vitro screening, in addition to larger animal models that more closely recapitulate human physiology.…”
Section: The Importance Of the Pc In Clinical Trialsmentioning
confidence: 99%
“…The second step is to study the effect of PC on the therapeutic performance of nanocarriers such as drug release. This should be done by incorporating more physiological 3D in vitro models [218] and systems that incorporate flow [219,220], mechanical forces [221][222][223], and multicellular populations [224,225] for in vitro screening, in addition to larger animal models that more closely recapitulate human physiology.…”
Section: The Importance Of the Pc In Clinical Trialsmentioning
confidence: 99%
“…Lung compliance provides a functional measure of the ability of the lungs to distend and is highly dependent on extracellular matrix composition, tissue architecture, spatial heterogeneities, surface tension-mediated alveolar recruitment and de-recruitment, and tidal volume. 14 Rrs levels of CDH model rabbits were higher than those of term infants and comparable to that in preterm infants. 15 They also demonstrated that Rrs levels did not vary significantly in the time series from birth.…”
Section: Discussionmentioning
confidence: 64%
“…In our study, the patients with Crs ≤0.22 mL/cmH 2 O/kg died. Lung compliance provides a functional measure of the ability of the lungs to distend and is highly dependent on extracellular matrix composition, tissue architecture, spatial heterogeneities, surface tension‐mediated alveolar recruitment and de‐recruitment, and tidal volume 14 . Low compliance in CDH indicates a reduced lung capacity and ventilation due to suppressed lung expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The patterned PDMS microfluidic mold was attached to a freshly prepared calcite (104) cleavage surface using a 3D-printed clamp , (Figure ). The clamp was created with polymethacrylate oligomer/monomer blend using a Form 2 printer (Formlabs Inc.).…”
Section: Methodsmentioning
confidence: 99%